Integrated Traditional Chinese and western medicine nursing for a patient with diabetic retinopathy complicated with traction retinal detachment (1例糖尿病视网膜病变合并牵拉性视网膜脱离患者的中西医结合护理体会) - JIANG Ying (江颖); WANG Luxia (王璐霞); LI Yajing (李亚静); JIA Shaohong (贾少宏); NIE Guiyun (聂桂云); LIU Honghong (刘红红); NI Chunxia (倪春霞) (中西医结合护理)
This paper summarized the key points of integrated Traditional Chinese and western medicine nursing for a patient with diabetic retinopathy complicated with traction retinal detachment. Targeted nursing interventions included body positioning care, exercise guidance, eye nursing, psychological care and lifestyle care. In addition, Traditional Chinese Medicine nursing techniques including auricular acupoint pressing, acupoint massage, cupping and wrist-ankle acupuncture were carried out to relieve the clinical symptoms and improve the postoperative rehabilitation of the patient. (总结1例糖尿病视网膜病变合并牵拉性视网膜脱离患者的术后中西医护理要点。围手术期间开展体位与活动护理、眼部护理、心理护理、生活护理等多项针对性护理措施, 同时配合耳穴压丸、穴位按摩、拔罐、腕踝针等中医护理技术, 旨在确保手术治疗效果, 改善临床症状和促进术后康复。)